2020
DOI: 10.7554/elife.58873
|View full text |Cite
|
Sign up to set email alerts
|

Genome expansion in early eukaryotes drove the transition from lateral gene transfer to meiotic sex

Abstract: Prokaryotes acquire genes from the environment via lateral gene transfer (LGT). Recombination of environmental DNA can prevent the accumulation of deleterious mutations, but LGT was abandoned by the first eukaryotes in favour of sexual reproduction. Here we develop a theoretical model of a haploid population undergoing LGT which includes two new parameters, genome size and recombination length, neglected by previous theoretical models. The greater complexity of eukaryotes is linked with larger genomes and we d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 72 publications
(125 reference statements)
1
23
0
Order By: Relevance
“…DNA exchange via these HGT mechanisms provides for diversity generation within a bacterial population; and thus, they provide the same advantages as sex in eukaryotic organisms and can be thought of analogous processes [ 53 , 54 ]. Recently Colnaghi et al [ 55 ] demonstrated that eukaryotic sex developed to provide the same population-level benefits as HGT in prokaryotes, including protection form Muller's ratchet, because as genome size increased there was a need for increases in recombination length. Without the ability to rapidly generate diversity, all individuals within the population would have the same fitness level with respect to environmental challenges which would decrease a population's chance of survival during times of environmental change.…”
Section: Current Perspectivementioning
confidence: 99%
“…DNA exchange via these HGT mechanisms provides for diversity generation within a bacterial population; and thus, they provide the same advantages as sex in eukaryotic organisms and can be thought of analogous processes [ 53 , 54 ]. Recently Colnaghi et al [ 55 ] demonstrated that eukaryotic sex developed to provide the same population-level benefits as HGT in prokaryotes, including protection form Muller's ratchet, because as genome size increased there was a need for increases in recombination length. Without the ability to rapidly generate diversity, all individuals within the population would have the same fitness level with respect to environmental challenges which would decrease a population's chance of survival during times of environmental change.…”
Section: Current Perspectivementioning
confidence: 99%
“…For prokaryotes, in particular, recent studies have suggested that natural transformation may play an important role in the removal (rather than the acquisition) of mobile elements [ 56 , 57 ]. Furthermore, it is possible that the mechanisms of genetic exchange (sex and/or HGT) are themselves under selection for other reasons, such as the optimal recombination length [ 23 ]. Preliminary results for example indicate that a strong deletion bias promotes genome streamlining irrespective of the dynamics of transposons, but TE-induced DNA damage still has a major impact on genome dynamics (electronic supplementary material, figure S9).…”
Section: Discussionmentioning
confidence: 99%
“…Transformation is one of the major routes of genetic exchange via LGT in bacteria and involves the acquisition of environmental DNA (eDNA), followed by recombination into the host genome ( 8 , 9 ). By allowing genetic exchange between lineages, transformation can restore genes that have been disrupted through mutation or deletion ( 10 12 ), counter the effects of genetic drift and reverse Muller’s ratchet ( 11 , 13 ), and accelerate adaptation by reducing selective interference ( 14 , 15 ). Previous modeling work has shown that the expansion of early eukaryote genome size was likely to have caused the failure of LGT ( 13 ).…”
mentioning
confidence: 99%
“…By allowing genetic exchange between lineages, transformation can restore genes that have been disrupted through mutation or deletion ( 10 12 ), counter the effects of genetic drift and reverse Muller’s ratchet ( 11 , 13 ), and accelerate adaptation by reducing selective interference ( 14 , 15 ). Previous modeling work has shown that the expansion of early eukaryote genome size was likely to have caused the failure of LGT ( 13 ). While LGT via transformation helps to purge deleterious mutations ( 11 ), this benefit rapidly wanes as genome size increases because of the difficulty of matching individual mutations with eDNA ( 13 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation